(untitled) - VUFO-NGO resource centre (Hà Nội, 2008)
This is the result from 20 sectors-specific Working Groups (WGs) operating under the NGO RC in 2008, including the newly established thematic groups under the Ho Chi Minh NGO Discussion group, each focusing on a specific area of development work in Vietnam.
Keywords: Non-governmental organizations,Rural development,Tổ chức phi chính phủ,Phát triển nông thôn